2020
DOI: 10.1101/2020.11.23.395327
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The novel PII-interacting protein PirA regulates flux into the cyanobacterial ornithine-ammonia cycle

Abstract: Among prokaryotes, cyanobacteria have an exclusive position due to the fact that they perform oxygenic photosynthesis. Cyanobacteria substantially differ from other bacteria in further aspects, e.g. they evolved a plethora of unique regulatory mechanisms to control primary metabolism. This is exemplified by the regulation of glutamine synthetase (GS) via small proteins termed inactivating factors (IFs). Here we reveal another small, 51 amino acid protein, which is encoded by the ssr0692 gene, to regulate flux … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
(137 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, 10 of the 65 upregulated genes in the DsbtB mutant were upregulated in WT cells only after a shift to LC conditions. This group includes the genes encoding the glutamine synthetase inactivation factors IF7 and IF17 (that are involved in the downregulation of N-assimilation (Brandenburg & Kl€ ahn, 2020)) and the PII-interacting regulator of arginine synthesis (PirA) (Bolay et al, 2021). Furthermore, six of the 65 upregulated genes in the DsbtB mutant became downregulated in WT cells post LC shift (Fig.…”
Section: Gene Expression Analysiscomparison Of Dsbtb and Wtmentioning
confidence: 99%
“…Interestingly, 10 of the 65 upregulated genes in the DsbtB mutant were upregulated in WT cells only after a shift to LC conditions. This group includes the genes encoding the glutamine synthetase inactivation factors IF7 and IF17 (that are involved in the downregulation of N-assimilation (Brandenburg & Kl€ ahn, 2020)) and the PII-interacting regulator of arginine synthesis (PirA) (Bolay et al, 2021). Furthermore, six of the 65 upregulated genes in the DsbtB mutant became downregulated in WT cells post LC shift (Fig.…”
Section: Gene Expression Analysiscomparison Of Dsbtb and Wtmentioning
confidence: 99%
“…Very recently, it was shown that Ssr0692 (51 aa, 5.8 kDa) is required to balance the synthesis of arginine and several other key amino acids under fluctuating N conditions. Indeed, the protein was confirmed to interact with PII and was hence named PII-interacting regulator of arginine synthesis (PirA, [80]).…”
Section: Pii As An Antagonist For the Interaction Of Small Proteins Wmentioning
confidence: 99%